2016
DOI: 10.1074/jbc.m115.702092
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Bidirectionally Modulates Macrophage Polarization and Epigenetically Regulates Macrophage Memory

Abstract: Macrophages are pleiotropic cells capable of performing a broad spectrum of functions. Macrophage phenotypes are classified along a continuum between the extremes of proinflammatory M1 macrophages and anti-inflammatory M2 macrophages. The seemingly opposing functions of M1 and M2 macrophages must be tightly regulated for an effective and proper response to foreign molecules or damaged tissue. Excessive activation of either M1 or M2 macrophages contributes to the pathology of many diseases. Emodin is a Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 60 publications
4
45
0
Order By: Relevance
“…S. Gao and S. Iwanowycz, et al . have reported that several Chinese herb-derived antioxidants, such as Curcumin and Emodin, could suppress the excessive response of M1 macrophages via blockade of NF-κB signaling pathway2044454647. But others indicated that NF-κB activation plays an important role in macrophage differentiation toward the M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…S. Gao and S. Iwanowycz, et al . have reported that several Chinese herb-derived antioxidants, such as Curcumin and Emodin, could suppress the excessive response of M1 macrophages via blockade of NF-κB signaling pathway2044454647. But others indicated that NF-κB activation plays an important role in macrophage differentiation toward the M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It also down-regulates CXCR4 to suppress C-X-C motif chemokine 12 (CXCL-12)-induced cell migration and invasion in hepatocellular carcinoma HepG2 and HepG3 cells [395]. In addition, emodin inhibits the differentiation of maturation of DCs [396], and can modulate macrophage polarization to restore macrophage homeostasis [397].…”
Section: Emodinmentioning
confidence: 99%
“…Collectively, histones modifications of genes required for M1 or M2 polarization might have the therapeutic potential in various pathologies. For example, emodin seemingly to bidirectionally restore macrophage M1/M2 polarization and immune homeostasis by inhibiting the removal of H3K27 trimethylation (H3K27me3) and the addition of H3K27 acetylation (H3K27ac), respectively [ 117 ]. Ornithine decarboxylase (ODC) could inhibit gastric and colonic inflammation by the deletion of M1 macrophage responses, which accompanied by the decreased H3K4 monomethylation, H3K9 acetylation and increased H3K9 di/trimethylation in primary macrophages [ 113 ].…”
Section: Histone Modificationmentioning
confidence: 99%